Comprehensive Characterization of Secondary Metabolites in Fruits and Leaves of Cloudberry (Rubus chamaemorus L.) - Anna V. Faleva; Nikolay V. Ul’yanovskii; Aleksandra A. Onuchina; Danil I. Falev; Dmitry S. Kosyakov (Metabolites, 2023)
Cloudberry (Rubus chamaemorus L.) is a circumpolar boreal plant rich in bioactive compounds and is widely used in food and in folk medicine. In this study, a combination of two-dimensional NMR spectroscopy and liquid chromatography–high-resolution mass spectrometry was used for the comprehensive characterization of secondary metabolites in cloudberry lipophilic and hydrophilic extracts. Special attention was paid to the leaf extractives, which are highly enriched in polyphenolic compounds, the content of which reaches 19% in the extract (in gallic acid equivalent). The chemical composition of the polyphenolic fraction is represented mainly by the glycosylated derivatives of flavonoids, hydroxycinnamic (primarily caffeic), gallic (including the structure of galloyl ascorbate) and ellagic acids, catechin, and procyanidins. The contents of aglycones in the polyphenolic fraction were 64 and 100 mg g−1 for flavonoids and hydroxycinnamic acids, respectively, while the content of free caffeic acid was 1.2 mg g−1. This determines the exceptionally high antioxidant activity of this fraction (750 mg g−1 in gallic acid equivalent) and the ability to scavenge superoxide anion radicals, which is 60% higher than that of Trolox. The lower polar fractions consist mainly of glycolipids, which include polyunsaturated linolenic acid (18:3), pentacyclic triterpenic acids, carotenoid lutein, and chlorophyll derivatives, among which pheophytin a dominates. Along with the availability, the high antioxidant and biological activities of cloudberry leaf extracts make them a promising source of food additives, cosmetics, and pharmaceuticals.